PROBA-3 mission. (1st January 2013) - Tarabini Castellani, Lorenzo; Llorente, Jesús Salvador; Fernández Ibarz, José María; Ruiz, Mercedes; Mestreau-Garreau, Agnes; Cropp, Alexander; Santovincenzo, Andrea
PROBA-3 is the ESA mission devoted to the demonstration of precise formation flying technology. Precise formation flying will allow small spacecraft, flying with a fixed relative geometry, to synthesise giant structure-less instruments. PROBA-3 consists of two satellites keeping a formation from 25 to 250 metres controlling relative position with about one millimetre accuracy. The spacecraft will autonomously manage the formation and take mission critical decision with no ground supervision. The metrology sensors chain will allow formation acquisition and relative position determination maintenance with micrometric precision. Periodic in flight automatic calibration will compensate the systematic deformation induced by the space environment. This paper details the mission objectives and the challenging requirements. It describes the overall mission design and in particular the formation flying technology demonstration plan. The main mission novelties are highlighted and the mission autonomy, formation flying sensors and algorithms and verification approaches are introduced. The preliminary performance results are presented. Eventually, the potential exploitation of the PROBA-3 demonstration for future missions is presented in the conclusions.